Pelaksanaan Terapi Wicara dan Terapi Sensori Integrasi pada Anak Terlambat Bicara - Sunanik, Sunanik (Nadwa, 2013)
The background of this research is the idea that a speech and language disorder is the causes of developmental disorders that are commonly found in children. Such disorder increases rapidly. Some reports put a number of speech and lan-guage disorder in the ranges from 5-10% in school children. This makes the speech delay as the most common disorder in childhood, so that quick treatment and appropriate therapy are highly needed for children with speech delay. The therapies made are speech therapy and sensory integration. The implementation of speech therapy and sensory integration should be given to children as early as possible. Speech therapy and sensory integration in children with speech delay have important role in determining the childs language development and motor skills. Inclusive education is education that puts all learners with special needs in the regular school day. In this kind of education, teachers have full responsi-bility for learners with special needs.